Rare case of ocular tuberculous noduloulcerative scleritis - Mridula, Pentapati; Shah, Suchi; Babu, Gangasagara Suresh (International Journal of Medical Research and Review, 2015)
Tuberculosis is an endemic disease in developing countries like India. A scleral tuberculoma is a very rare manifestation of this disease. Ocular involvement is usually secondary to pulmonary tuberculosis or in cases of disseminated tuberculosis. A very high index of suspicion is necessary in endemic areas as the condition can be sight threatening. We hereby report a rare case of ocular tuberculosis presenting as a noduloulcerative lesion of the sclera. An otherwise healthy, 26 year old female patient, presented with redness, pain and watering in the right eye since two months. On examination an oval noduloulcerative scleral lesion was noted associated with cells and flare in the anterior chamber. Patient had a normal vision and posterior segment. After ruling out all other causes of ocular inflammation and with a positive Mantoux test, the patient was started on oral antituberculous treatment. The lesion faded and resolved over a period of two weeks. This case emphasises the necessity of ruling out tuberculosis in endemic areas where the clinical manifestations of the disease can be obscure. Early diagnosis and prompt systemic treatment gives a favourable prognosis.